Implikasi Perkawinan Anak Terhadap Perlindungan Hak Anak di Kota Samarinda - Lida Khalisa Budhaeri; Erna Susanti; Rini Apriyani (Jurnal Hukum Lex Generalis, 2025)
Child marriage is a social phenomenon that is rampant in the community, child marriage can be seen as a violation of the protection of children's rights and human rights that are contrary to various legal provisions and international agreements. The research method used is a Social Legal approach. The results of the study show that child marriage still occurs in marriage dispensations with various causal factors and tends to increase in Samarinda City. Marriage dispensations can legalize child marriage, which has the potential to violate children's rights, so it is necessary to carry out protective efforts as a form of prevention that must be carried out repressively and preventively as a form of security and comfort in protecting, maintaining and defending their rights.